Achieving High Stability and Performance in P2‐Type Mn‐Based Layered Oxides with Tetravalent Cations for Sodium‐Ion Batteries. Issue 19 (13th April 2022) - Vanaphuti, Panawan; Yao, Zeyi; Liu, Yangtao; Lin, Yulin; Wen, Jianguo; Yang, Zhenzhen; Feng, Zimin; Ma, Xiaotu; Zauha, Anna C.; Wang, Yan; Wang, Yan
Abstract: P2‐type sodium‐manganese‐based layered cathodes, owing to their high capacity from both cationic and anionic redox, are a potential candidate for Na‐ion batteries (NIBs) to replace Li‐ion technology in certain applications. Still, the structure instability originating from irreversible oxygen redox at high voltage remains a challenge. Here, a high sustainability cobalt‐free P2‐Na0.72 Mn0.75 Li0.24 X0.01 O2 (X = Ti/Si) cathode is developed. The outstanding capacity retention and voltage retention after 150 cycles are obtained in half‐cells. The finding shows that Ti localizes on the surface while Si diffuses to the bulk of the particles. Thus, Ti can act as a protective layer that alleviates side reactions in carbonate‐based electrolyte. Meanwhile, Si can regulate the local electronic structure and suppress oxygen redox activities. Notably, full‐cells with hard carbon (≈300–335 W h kg −1 based on the cathode mass) deliver the capacity retention of 83% for P2‐Na0.72 Mn0.75 Li0.24 Si0.01 O2 and 66% for P2‐Na0.72 Mn0.75 Li0.24 Ti0.01 O2 after 500 cycles; this electrochemical stability is the best compared to other reported cathodes based on oxygen redox at present. The superior cycle performance also stems from the ability to inhibit microcracking and planar gliding within the particles. Altogether, this finding offers a new composition for developing high‐performance low‐cost cathodes for NIBs and highlights the unique role of Ti/Si ions. Abstract : P2‐type sodium‐manganese‐based layered cathodes (P2‐NMO), owing to their high‐specific capacity, are a potential candidate for sodium‐ion batteries to replace lithium‐ion technology in certain applications. Still, structural instability remains a challenge. This work not only proposes low‐cost P2‐NMO compositions, but also highlights the distinctive role of Ti/Si ions in the future development of high‐energy‐density cathode materials for sodium‐ion batteries.